2018
DOI: 10.1002/qre.2400
|View full text |Cite
|
Sign up to set email alerts
|

A novel pseudo‐maximum likelihood estimation method for accelerated degradation tests under Wiener process

Abstract: For reliability assessment based on accelerated degradation tests (ADTs), an appropriate parameter estimation method is very important because it affects the extrapolation and prediction accuracy. The well‐adopted maximum likelihood estimation (MLE) method focuses on interpolation fitting and obtains results via maximizing the likelihood of the observations. However, a best interpolation fitting does not necessarily yield a best extrapolation. In this paper, therefore, a pseudo‐MLE (P‐MLE) method is proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…where Φ GA (⋅|𝑎𝑡 𝑏 , 𝛽) represents the CDF of gamma distribution Γ(𝑎𝑡 𝑏 , 𝛽), Φ 𝐹 (⋅|2𝑎𝑡 𝑏 , 2𝛿) represents the CDF of F distribution associated with the degree of freedom 2𝑎𝑡 𝑏 and 2𝛿, and Φ IG (⋅|𝜇𝑡 𝑏 , 𝜂𝑡 2𝑏 ) represents the CDF of inverse Gaussian distribution IG(𝜇𝑡 𝑏 , 𝜂𝑡 2𝑏 ). Similarly, the CDF of TGP model can be found in Equation (7), denoted by 𝐹 TGP (𝑡). Figure 3 displays four estimated CDFs, where black dots represent the empirical CDF 𝐹 * (𝑡), and the red, violet, blue, and black curves represent FGP (𝑡) FREGP (𝑡), FIGP (𝑡), and FTGP (𝑡) with their corresponding 95% CIs (Algorithm 2), respectively.…”
Section: Fatigue Crack Growth Data In Lu and Meeker 20mentioning
confidence: 99%
See 1 more Smart Citation
“…where Φ GA (⋅|𝑎𝑡 𝑏 , 𝛽) represents the CDF of gamma distribution Γ(𝑎𝑡 𝑏 , 𝛽), Φ 𝐹 (⋅|2𝑎𝑡 𝑏 , 2𝛿) represents the CDF of F distribution associated with the degree of freedom 2𝑎𝑡 𝑏 and 2𝛿, and Φ IG (⋅|𝜇𝑡 𝑏 , 𝜂𝑡 2𝑏 ) represents the CDF of inverse Gaussian distribution IG(𝜇𝑡 𝑏 , 𝜂𝑡 2𝑏 ). Similarly, the CDF of TGP model can be found in Equation (7), denoted by 𝐹 TGP (𝑡). Figure 3 displays four estimated CDFs, where black dots represent the empirical CDF 𝐹 * (𝑡), and the red, violet, blue, and black curves represent FGP (𝑡) FREGP (𝑡), FIGP (𝑡), and FTGP (𝑡) with their corresponding 95% CIs (Algorithm 2), respectively.…”
Section: Fatigue Crack Growth Data In Lu and Meeker 20mentioning
confidence: 99%
“…In addition, the Wiener process is usually implemented to analyze the non-monotonic degradation data (Doksum and Hóyland 4 ). More descriptions for Wiener process model can be referred to Wang, 5 Chhikara and Folks, 6 Wang et al, 7 Whitmore, 8 and Whitmore and Schenkelberg. 9 The GP is an applicative method to fit the monotonically increasing degradation path.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that using the proposed method under Bayes D-optimality not only improves the accuracy of model parameters but also eliminates the impact of model uncertainty. Wang et al 32 proposed a pseudo-Maximum Likelihood Estimate (p-MLE) method to improve the prediction accuracy of model parameters to address the problem of failing to obtain the best extrapolation results using the best interpolation fitting model parameters. Example verification revealed that the proposed method may not achieve the maximum likelihood under the condition of limited sample size but can improve the prediction accuracy of the reliability of tested products.…”
Section: Introductionmentioning
confidence: 99%